Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Putri, Resti Amelia; Maryani, Maryani; Damayanti, Damayanti (Penerbit Goodwood, 2023)
Purpose: The purpose of this study is to investigate the impact of value-added capital, value-added human capital, and structural capital value-added on the financial performance of food and beverage companies listed on the Indonesia Stock Exchange. This study's variables include independent variables such as Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA), as well as the dependent variable Financial Performance. Method: This quantitative study employed statistical tests on secondary data. Purposive sampling was used to select the samples. This study used 16 companies as samples over a four-year research span to collect 64 sample data units. Multiple linear regression analysis was employed in this study as an analytical method. Result: The findings revealed that there was a significant effect on financial performance from Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA) all at the same time, with only Value Added Capital Employed (VACA) and Structural Capital Value Added (STVA) having a significant influence. Contribution: This study suggests that companies can improve their financial performance by using their intellectual resources. Companies are expected to be able to manage their intellectual capital resources better, and efficient intellectual capital management can provide value added to support companies in improving their financial performance.